Engineering single-atom angular momentum eigenstates in an optical tweezer - Lunt, Philipp; Hill, Paul; Reiter, Johannes; Preiss, Philipp; Galka, Maciej; Jochim, Selim (Physical review, 2024)
We engineer angular momentum eigenstates of a single atom by using an all-optical approach based on the interference of Laguerre-Gaussian beams. We confirm the imprint of angular momentum by measuring the two-dimensional density distribution and by performing Ramsey spectroscopy in a slightly anisotropic trap, which additionally reveals the sense of rotation. This article provides the experimental details on the quantum state control of angular momentum eigenstates reported in P. Lunt et al., Phys. Rev. Lett. 133, 253401 (2024).
Gesehen am 09.10.2025